Food Waste on Foodservice: An Overview through the Perspective of Sustainable Dimensions - Maísa Lins; Renata Puppin Zandonadi; António Raposo; Veronica Cortez Ginani (Foods, 2021)
Food waste (FW) is a current, complex, and widely debated issue in various spheres of society. Globally, about 2.6 trillion dollars per year is lost because of wasted food. Part of FW is preventable, and it is necessary to identify where it occurs. In most cases, FW occurs at the end of the production chain (meal preparation and distribution). Identifying the main food service failures on FW is important for developing efficient strategies for reducing them. Therefore, this study aimed to perform a narrative review of the impacts caused by FW in food services considering the three dimensions of sustainability (social, economic, or environmental). Multiple reasons were identified in this review that impacts those three dimensions, such as the cost of wasted raw material, use of cleaning material, the energy consumption, salary of food handlers, the water footprint, the amounts of rest-intake, production waste, energy density wasted, use of organic food, and food donation. Identifying these aspects can contribute to reduce FW impacts for better sustainable development, develop tools to measure FW, and assist food service managers in minimizing FW.